OUTSTANDING RUSSIAN SCIENTISTS: DIMITRY AND ELENA WENTZEL - V. I. LEVIN (Высшее образование в России)
The paper presents the scientific biographies of two outstanding Soviet mathematicians and teachers Elena Sergeevna and Dimitry Alexandrovich Wentzel. The main attention is paid to the restoration of genuine events related to the scientific, pedagogical and social activities of these people. The paper extensively uses published materials, as well as oral memoirs of the participants of these events – friends and acquaintances of our heroes. Special attention is paid to the history and activities of the country’s largest military university – the Air Force Engineering Academy named after Zhukovsky (VVIA). Almost the whole life of the Wentzels was closely connected with the Academy. The life and customs of the Petersburg (Petrograd) University in the 1920s are described in detail, where E.S. Wentzel learned. The paper provides the information about many famous professors and teachers of both universities, reconstructs and analyzes the pedagogical activities of E.S. Wentzel in VVIA and MIIT (Moscow), her scientific and publishing activities in the field of probability theory and operations research. The author reconstructs and dwells on her literary activity under a pen name I. Grekova. As a writer, E.S. Wentzel contacted with the famous literary men (A.T. Tvardovsky, K.I. Chukovsky, A. Galich, etc.). The paper also describes the scientific activity of D.A. Wentzel in the field of ballistics, his contribution to publishing textbooks for military universities, his experience in training highly qualified personnel (candidates, doctors, academicians), his scientific and organizational activities (the creation of the Faculty of Armaments in the VVIA, the foundation of the Academy of Artillery Sciences of the USSR and others). The special aim of the paper was to recreate the human images of Elena and Dimitry Wentzel.